Achieving Multilateral Investment Court Through EU-ASEAN Expansion of Bilateral Investment ‘Court’: Is It Possible? - Permana, Rizky Banyualam (UI Scholars Hub, 2019)
Legitimacy of international investment law is in crisis. One particular area of international investment law that has been progressively re-developed is the area of investment dispute settlement. The EU sees the multilateral investment court as a proper solution to reform ISDS in the future. To achieve this final goal, starting from the bilateral level, the EU has included investment court provisions as an ISDS mechanism in its latest trade and investment agreement with its trading partners, among others, EU-Viet Nam FTA and IPA, as well as EU-Singapore FTA & IPA. This paper addresses central questions on how could existing investment court system in EU and ASEAN member states’ Investment Protection Agreements (IPA) can be expanded towards multilateral investment court in the future, and what are the challenges that can be expected from such expansion. It critically analyses concluded agreements between the EU and some of ASEAN Member States. I argue that for now, it is unlikely that multilateral investment court expansion will happen soon considering the challenges and concerns expressed by both sides.